2017
DOI: 10.5005/jp-journals-10005-1462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Health Status and Knowledge on Oral Health in Two Age Groups of Schoolchildren: A Cross-sectional Study

Abstract: Introduction: Oral health plays a pivotal role in the overall wellbeing of children. As children grow, there is a variation in their oral health status due to the changing trends and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…This figure certainly has a significant influence on the dental health status of students in Islamic boarding schools in Medan City. Late teen have better knowledge of oral health, but oral hygiene practices are not followed effectively (Geethapriya & Kandaswamy, 2017). There is no relationship between knowledge with attitude dental and oral health maintenance, in line with our study obtained are still many students who have dental care attitude despite they already know.…”
Section: Resultssupporting
confidence: 72%
“…This figure certainly has a significant influence on the dental health status of students in Islamic boarding schools in Medan City. Late teen have better knowledge of oral health, but oral hygiene practices are not followed effectively (Geethapriya & Kandaswamy, 2017). There is no relationship between knowledge with attitude dental and oral health maintenance, in line with our study obtained are still many students who have dental care attitude despite they already know.…”
Section: Resultssupporting
confidence: 72%
“…Older children tend to be independent toothbrushers and therefore more likely to brush twice or more a day. However, Geethapriya et al (2017) and Butten et al (2020) reported no significant improvement in oral health practices in older children, supposedly due to complacency or lack of encouragement by parents.…”
Section: Discussionmentioning
confidence: 87%
“…Oral health plays a pivotal role in the overall wellbeing and there is a variation in oral health status due to the changing trends and lifestyle. 11 Oral diseases can be considered a public health problem due to their high prevalence and significant social impact. 12 Mostly young population are involved in poor health maintenance.…”
Section: Discussionmentioning
confidence: 99%